BLUEBERRY JUICE ENCAPSULATED ON MALTODEXTRIN: THE IMPACT ON THE PROPERTIES OF WHITE CHOCOLATE - Lončarević, Ivana; Stožinić, Milica; Pajin, Biljana; Nikolić, Ivana; Petrović, Jovana; Šojić, Branislav; Zarić, Danica (Food and Feed Research, 2023)
The lower content of phenolic compounds in white chocolate makes this confectionery product unhealthier and, thus, adequate for enrichment compared to other types of chocolates like dark or milk. Less phenolics in white chocolate is due to absence of dark cocoa solids, abundant in these compounds. This study aimed to develop a new product with a higher nutritional value than regular white chocolate by enriching white chocolate with blueberry juice as a natural source of polyphenols. Since phenolic compounds are highly sensitive to heat, light, oxygen, and pH, encapsulated form of blueberry juice was used to increase their stability in the product. Blueberry juice was encapsulated on maltodextrin (B/M) and added to white chocolate at 80 g/kg and 100 g/kg concentrations. Enrichment significantly (p<0.05) increased the content of total dietary fibres and carbohydrates in the white chocolate and decreased proteins and total fats. The addition of the encapsulates significantly (p<0.05) impacted all particle size parameters, especially volume-weighted mean D[3,4] which increased (14.38 μm for B/M80 and 16.00 μm for B/M100) compared to the control (13.06 μm). Rheological properties are of great importance for products like chocolate and the incorporation of the encapsulates significantly (p<0.05) increased the values of rheology parameters like Casson viscosity (1.04 Pa∙s for B/M80 and 1.21 Pa∙s for B/M100). Likewise, enrichment significantly (p<0.05) decreased the hardness of the sample (B/M80) compared to the control. Furthermore, the content of total polyphenols and antioxidant capacity significantly (p<0.05) increased following the added concentration of the encapsulates. The highest content of total polyphenols and antioxidant capacity was observed in the chocolate sample enriched with 100 g/kg of encapsulate. The colour of the enriched samples significantly (p<0.05) differed from the control sample. The impact of the added encapsulate on sensory properties was not significant (p>0.05) except for the sweetness. The enriched chocolate samples were less sweet. The results of this study indicate the potential of maltodextrin as a carrier of sensitive bioactive compounds for the enrichment of products like white chocolate.